Creep study of glass reinforced polypropylene: Effect of temperature and presence of notches. (October 2021) - Kyzy, Bermet Kerim; Lanzutti, Alex; Magnan, Michele; Rondinella, Alfredo; Simonato, Michele; Furlanetto, Riccardo; Fedrizzi, Lorenzo
Highlights: Stress and temperature significantly decrease creep life of PP/GF30. Creep models can be used to describe the creep behavior of PP/GF30 plain specimens. Stress concentrations due to notches decreased the creep resistance of PP/GF30. The failure in notched specimens consists of crazing and quick crack propagation. Power-law models are used to estimate the time to failure of notched specimens. Abstract: Short fibers reinforced injection molded parts are commonly used in the applications under sustained loads. This requires creep resistance and creep behavior predictions under both short- and long-term service conditions. This article studies the creep behavior of injection molded polypropylene with short glass fibers at different temperatures and in the presence of a notch. The produced samples were analyzed by means of FT-IR (Fourier-transform infrared spectroscopy) and TGA (thermogravimetric analysis) to obtain and indication on microstructure and fiber content, respectively. Visible light microscopy was used to analyze the fiber orientation. Mechanical properties were measured using tensile testing. Tensile creep testing in an internally fabricated lever-type creep machine at a controlled constant temperature was conducted on plain specimens and specimens with machined notch. Fracture surfaces were analyzed by means of SEM (Scanning Electron Microscopy). Both creep strength and time to failure decrease with increasing temperature following the power law models. Norton's power law and Monkman-Grant's relationship can estimate the time to rupture not only of plain specimens, but also notched, if the stress is amplified by the stress concentration factor. These results can potentially estimate lifetime of injection molded parts with stress concentrations at elevated temperatures.